Integrative miRNA-mRNA profiling uncovers mechanisms of belimumab action in systemic lupus erythematosus - Royo, Maria; Joseph-Mullol, Blanca; Sandoval, Sebastian; Moliné, Teresa; Solé, Cristina; Cortés-Hernández, Josefina (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder driven by autoreactive B cells and characterized by the production of pathogenic autoantibodies. Belimumab, an anti-BAFF monoclonal antibody, has demonstrated efficacy in reducing disease activity and corticosteroid use in SLE patients, although responses remain variable. B-cell activating factor (BAFF) is essential for B cell survival and autoantibody production, positioning it as a key target in SLE pathogenesis. MicroRNAs (miRNAs), critical regulators of gene expression and immune homeostasis, have an emerging role in SLE pathophysiology. However, their regulation in response to anti-BAFF therapies, such as belimumab, remains unexplored. This study investigates miRNA-mRNA interactions in T cells, B cells, and myeloid cells from SLE patients before and after belimumab treatment. A total of 79 miRNAs associated with treatment response and 525 miRNA-gene interactions were identified. Validation in 18 SLE responders revealed significant changes in miRNA expression in T and myeloid cells, but not in B cells. Belimumab was found to modulate B cell development by regulating genes such as BLNK, BANK1, and MEF2C, as well as the CD40/CD40L axis. In T cells, miRNAs influenced interferon signaling and inflammatory cytokines via NF-κB activation. Changes in myeloid cells, characterized by the downregulation of KLF13, CCL5, and IL4, appear to be secondary to T cell modulation. These findings provide novel insights into the miRNA-mediated regulatory networks underlying belimumab’s immunomodulatory effects in SLE. Further research is required to validate these findings and through in vitro experiments to better understand the role of miRNAs in guiding treatment responses.